Implementation and violations of election principles in the 2024 Presidential and Vice-Presidential elections of the Republic of Indonesia - Eny Kusdarini; Puji Wulandari Kuncorowati; Nurdiyana Nurdiyana; Ali Masykur Fathurrahman (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
This study examines the implementation of electoral principles mandated in Article 22E of the 1945 Constitution—direct, universal, free, confidential, honest, and fair elections—in the 2024 Indonesian presidential and vice-presidential elections, which were marked by legal controversy following Constitutional Court Decision Number 90/PUU-XXI/2023. A socio-legal approach was employed, combining document analysis, in-depth interviews, and focus group discussions with election organisers and supervisory bodies. Data were analysed qualitatively using the Miles, Huberman, and Saldana interactive model, involving data reduction, display, and conclusion drawing. The principles of direct and universal suffrage were generally upheld. However, the principles of free, confidential, honest, and fair elections were only partially implemented. Violations identified include money politics, lack of institutional neutrality, power intervention, and vote mobilisation practices. These findings indicate persistent structural weaknesses in Indonesia’s electoral democracy, particularly in the 2024 elections. The study highlights the urgent need for strengthening institutional integrity, improving coordination among supervisory bodies, and enforcing election law more effectively. Enhancing public participation and oversight mechanisms is essential to ensure the full realisation of democratic electoral principles in future elections.